SOD1 Promotes Cell Proliferation and Metastasis in Non-small Cell Lung Cancer via an miR-409-3p/SOD1/SETDB1 Epigenetic Regulatory Feedforward Loop - Liu, Shilong; Li, Bin; Xu, Jianyu; Hu, Songliu; Zhan, Ning; Wang, Hong; Gao, Chunzi; Li, Jian; Xu, Xiangying (Frontiers in Cell and Developmental Biology, 2020)
Superoxide dismutase 1（SOD1）is a major antioxidant with oncogenic effects in many human cancers. SOD1 is overexpressed in various cancers; however, the clinical signiﬁcance and functions of SOD1 in non-small cell lung cancer (NSCLC), particularly epigenetic regulation of SOD1 in NSCLC carcinogenesis and progression and have been less well investigated. In this study, we verified that SOD1 expression was upregulated in NSCLC cell lines and tissues. Further, elevated SOD1 expression could promote NSCLC cell proliferation, invasion and migration. Moreover, inhibition of SOD1 expression induced NSCLC cell cycle G1 phase arrest and promoted apoptosis. In addition, miR-409-3p could repress SOD1 expression and significantly counteract its oncogenic activities. Elevated expression of SOD1 could also repress methylation levels in lung cancer. Bioinformatics analysis indicated that SET domain bifurcated histone lysine methyltransferase1(SETDB1) was involved in regulation of miR-409-3p and SOD1 expression and functions in NSCLC cells as a epigenetic transcription factor. Identification of this miR-409-3p/SOD1/SETDB1 epigenetic regulatory feedforward loop may provide new insights to further understanding of NSCLC tumorigenesis and progression. Further, SOD1 is a potential new target for NSCLC treatment.